Pengembangan Bahan Ajar Bahasa Arab On-Line Berbasis Website Wakelet pada Program Intensif Pusat Pengembangan Bahasa UIN Maulana Malik Ibrahim Malang - Sahya Husein; Muhamad Abdul Hamid; M. Sayid Umar (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2020)
The results of this study: 1) The final product of this research and development is the Wakelet website-based online Arabic teaching material system designed using ADDIE (Analysis-Design-Development-implementation-Evaluation). The online teaching material application developed is designed for lectures for sixteen meetings (one semester for the weight of two credits) at the Language Development Center of UIN Maulana Malik Ibrahim Malang with the link https://wakelet.com/i/invite?isSpace=true&code= TbJlHI for 5th chapter and https://wakelet.com/i/invite?isSpace=true&code=QCvOWs for 6th chapter. 2) The test results on the components of Wakelet-based online Arabic teaching materials show that: learning design experts give an assessment that this is very good and makes it easier for students to learn Arabic online from their respective places. This is because this application is easy to operate on smartphones and laptops, does not require a lot of internet quota, and it also looks attractive.